The effects of dietary supplementation with ellagic acid on the growth performance, nutrient apparent metabolic rate, slaughter performance, and fecal microbiota diversity of young pigeons - Ren, Jie; Liang, Yafei; Ding, Mingcong; Li, Yuanhao; Zhao, Xiaoyu; Li, Haiying; Yang, Huiguo; Liu, Jiajia (Frontiers in Animal Science, 2026)
The purpose of this study was to evaluate the effects of ellagic acid (EA) supplementation on growth performance, apparent metabolic rate of nutrients, slaughter characteristics, and fecal flora diversity in American King Pigeons. As a natural polyphenolic compound, EA has potential application prospects in livestock and poultry breeding due to its multiple biological activities. This study aims to clarify the suitable supplementation level of EA in the diet of meat pigeons, so as to provide a theoretical basis for its rational application. A total of 192 29-day-old American King Pigeons, weighing 470 ± 10 g with equal numbers of males and females, were selected. The pigeons were randomly divided into four groups, with 6 replicates per group and 8 pigeons per replicate. The control group was fed a basal diet, while the test groups I, II, and III were supplemented with EA at 100 mg/kg, 200 mg/kg, and 400 mg/kg respectively. The experiment included a 4-day prefeeding period followed by a 28-day formal experimental period. Relevant indicators were determined after the formal period, and data were statistically analyzed with P < 0.05 considered significant. In terms of growth performance, the chest width and tibia length of test group III were significantlyhigher than those of other groups (P < 0.05), and the chest depth of test group III was significantly higher than that of test groups III and II (P < 0.05). For slaughter performance, the leg muscle weight and gizzard weight of test group III were significantly higher than those of the control group (P < 0.05), and the thymus weight and index of test group I were significantly higher than those of the control group (P < 0.05). Regarding immune cytokines, the GSH-Px activity of test group I was significantly higher than that of the control group (P < 0.05), the MDA content of test group III was significantly lower than that of the control group (P < 0.05), and the immunoglobulin IgA levels of test groups I and II were significantly higher than that of the control group (P < 0.05). For nitrogen metabolism and liver function indexes, the TP content of test group I was significantly higher than that of the control group (P < 0.05), and the AST activity of test group III was significantly lower than that of the control group (P < 0.05). As for fecal flora diversity, 200 mg/kg EA supplementation was beneficial to maintaining the richness and stability of intestinal microflora. In conclusion, adding ellagic acid to the diet can improve the growth performance, immunity, total protein level, and intestinal microflora stability of American King Pigeons. Different doses of EA exert specific effects: high dose (400 mg/kg) is superior in body size development and muscle deposition, low dose (100 mg/kg) focuses on immune enhancement, while medium dose (200 mg/kg) shows the most significant comprehensive effect. Therefore, 200 mg/kg is the suitable EA supplementation level for American King Pigeons.